ASUPAN ZAT-ZAT GIZI DAN KADAR GULA DARAH PENDERITA DM-TIPE2 DI POLIKLINIK PENYAKIT DALAM RSUD Dr. H. ABDUL MOELOEK PROVINSI LAMPUNG - Usdeka Muliani (Politeknik Kesehatan Tanjung Karang, 2013)
Usdeka Muliani1)1) Jurusan Gizi Poltekkes Kemenkes Tanjungkarange-mail : inideka@yahoo.co.idAbstract :The Corerelation between Intake of Nutrients With Blood Sugar Levels Patients DM-Tipe2 in Polyclinic RSUDDr.H Abdul Moeloek Lampung Province. Patients with DM in ambulatory RSUDAM) Lampung Province in 2011who ranks third out of 10 diseases most patients.The general objective of this study was to determine the relationship of intake of nutrients in the blood sugar levels in patients with DM-tipe2 polyclinic hospital medicine. RSUDAM. This research is experimental analytic cross sectional design. The population is patients with DM-poly tipe2 outpatient internal medicine RSUDAM Lampung province. Samples 57 people with accidental sampling technique. Data was analyzed by univariate and bivariate.The results of univariate analysis were 39 patients (68.4%) unfavorable energy intake, 63.2%patients poor protein intake, 52.6% patients good carbs intake, 61.4%patients unfavorable fat intake, 86% patients good cholesterol intake, and 68.4% patients of fiber intake is less than it should.The results of the bivariate analysis are known (1) There is a significant correlation between energy intake with blood sugar levels of p = 0,001, (2) There is a relationship between protein intake with blood sugar level (p = 0,033) and (3) There is a relationship between carbohydrate intake with blood sugar levels (p = 0,004) and (4) There is no relationship between the intake of fat to the blood sugar levels (p = 0,590), (5) There is no relationship with the intake of cholesterol in blood sugar levels (p = 0 ,422) , (6) There is a relationship of fiber intake with blood sugar levels (p = 0,001). Suggestions, better patients with DM in polyclinic RSUDAM gets counseling and nutritional counseling on a regular basis, as well as the need to do further research on the factors that influence food intake of people with DM-tipe2.Keywords : DM-Tipe2, Intake of nutrition, blood sugar levelsAbstrak : Hubungan Asupan Zat-Zat Gizi Dengan Kadar Gula Darah Penderita DM-Tipe2 di Poliklinik Penyakit Dalam RSUD Dr. H Abdul MoeloekProvinsi Lampung.Pasien DM di ruang rawat jalan RSUDAM Provinsi Lampung tahun 2011 menempati urutan ketiga dari 10 penyakit terbanyak. Tujuan penelitian, untuk mengetahui hubungan asupan zat-zat gizi dengan kadar gula darah penderita DM-tipe2 di poliklinik penyakit dalam RSUDAM Provinsi Lampung. Jenis penelitian analitik dengan rancangan cross sectional. Populasi, adalah pasien DM-tipe2 rawat jalan di poli penyakit dalam RSUDAM Provinsi Lampung. Sampel 57 orang dengan teknik accidental sampling.Data dianalisis secara univariat dan bivariat. Hasil analisis univariat68,4% pasien kurang baik asupan energinya, 63,2% pasien asupan protein kurang baik, 52,6% pasien baik asupan karbohidratnya, 61,4% pasien asupan lemak kurang baik, 86% pasien baik asupan kholesterol, dan 68,4% pasien asupan serat kurang dari seharusnya. Hasil analisis bivariat (1) Ada hubungan yang bermakna antara asupan energi dengan kadar gula darah (p= 0,001) ; (2) Ada hubungan antara asupan protein dengan kadar gula darah (p = 0,033) ; (3) Ada hubungan antara asupan karbohidrat dengan kadar gula darah (p= 0,004) ; (4) Tidak ada hubungan antara asupan lemak dengan kadar gula darah( p = 0,590) ; (5) Tidak ada hubungan asupan kholesterol dengan kadar gula darah (p=0,422) ; (6) Ada hubungan asupan serat dengan kadar gula darah (p = 0,001). Saran, sebaiknya pasien DM di poli penyakit dalam mendapat penyuluhan dan konseling gizi secara berkala, serta perlu dilakuka penelitian lebih lanjut mengenai faktor-faktor yang mempengaruhi asupan makanan penderita DM-tipe2.Kata kunci : DM-Tipe2, asupan zat-zat gizi, kadar gula darah